2009
DOI: 10.1126/science.1174605
|View full text |Cite
|
Sign up to set email alerts
|

Modern Riding Style Improves Horse Racing Times

Abstract: intact fresh cadaver forelimbs, 3) ROM of skeletal forelimbs including ligaments, but without muscles and 4) ROM based on joint surfaces of the forelimb bones. A literature study provided information for level 1. A cadaver study was performed by tracking bone-pins with reflective marker triads using a 6 camera system (Vicon) to calculate 3-D ROM for levels 2 and 3. Surface scans of the bones, made with a laser surface scanner (Faro), together with Software for Interactive Musculoskeletal Modelling gave the ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 8 publications
3
75
0
Order By: Relevance
“…6,[11][12][13][14][15][16] In our model the power produced by the runner ͓see Eq. ͑6͔͒ is used to accelerate the runner's body and to overcome air resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,[11][12][13][14][15][16] In our model the power produced by the runner ͓see Eq. ͑6͔͒ is used to accelerate the runner's body and to overcome air resistance.…”
Section: Discussionmentioning
confidence: 99%
“…͑See Ref. 6 for an analysis of the energy cost of the vertical movement in a horse race.͒ Also, the runners' velocity declines slightly close to the end of the 100 m race, which is not taken into account in Eq. ͑1͒.…”
Section: Modeling the Time Dependence Of The Velocitymentioning
confidence: 99%
“…Work on jockey position demonstrated how the modern jockey position increased the dampening effect of forces transmitted to the rider, stabilizing the rider's center of mass. 20 A novel study examining segment accelerations demonstrated that experienced show jumping athletes have smaller leg accelerations than novice athletes during a jumping task. They concluded that novice riders had a poor ability to maintain balance when absorbing the forces created during landing.…”
Section: Lower Extremitymentioning
confidence: 99%
“…11 During the same time span, 20.07%, 29.07% and 16.68% of all injuries were to the head, upper, and lower extremity, respectively in the NEISS data. 11 For ages [15][16][17][18][19][20][21][22][23][24]4.7% of injuries were to the head, 5.06% were to the upper extremity (shoulder, elbow, lower arm, wrist, upper arm, hand) and 3.86 % were to the lower extremity (knee, lower leg, ankle, foot, upper leg). 11 With regard to mechanism of injury (MOI), falling is the most commonly reported mechanism with manual labor related to the upkeep of the animal/facilities also contributing.…”
Section: Introductionmentioning
confidence: 99%
“…The modern 'martini glass' jockey position was introduced in the 19 th century and has been credited with a 5-7% reduction in race times (Pfau et al, 2009). In this position, 90% of the jockeys' mass is distributed over the withers (Fruehwirth et al, 2004), however, it has been proposed that jockeys are able to mitigate any deleterious effects by isolating their centre of mass ( of horse management and the ever-increasing campaign to improve horse and jockey welfare, the use of simulators to facilitate training and to aid in refining race jockey technique is increasingly common.…”
Section: Introductionmentioning
confidence: 99%